Model Advanced Organizer: Pengaruhnya Terhadap Kemampuan Berpikir Kreatif - Ernaeni, Listia; Gunawan, Indra (Universitas Islam Negeri Raden Intan Lampung, 2019)
Abstract: This study uses the type of Quasy Experiment Design with the design of Non Equivalent Control Group Design. The study used two classes as the experimental class and the control class. The study population was VII grade students. The sampling technique used is Cluster Random Sampling. Based on data analysis and discussion, there are differences in the average value of learning outcomes (posttest) between learning using the advanced organizer and conventional learning models, from the results of the t test also known that 0.044 less than0.05 which means H0 is rejected which indicates the influence of the model advanced organizer learning on students' creative thinking abilities.Abstrak: Penelitian ini menggunakan jenis Quasy Eksperiment Design dengan rancangan desain Non Equivalent Control Group Design. Penelitian menggunakan dua kelas sebagai kelas eksperimen dan kelas kontrol.. Populasi penelitian adalah peserta didik kelas VII. Teknik pengambilan sampel yang digunakan dengan cara Cluster Random Sampling. Berdasarkan analisis data dan pembahasan, terdapat perbedaan nilai rata-rata hasil belajar (postest) antara pembelajaran dengan menggunakan model pembelajaran advanced organizer dan konvensional, dari hasil perhitungan uji t juga diketahui bahwa 0,044 kurang dari 0,05 yang berarti H0 ditolak yang menunjukkan adanya pengaruh model pembelajaran advanced organizer terhadap kemampuan berpikir kreatif peserta didik.